Staphylococcus epidermidis glucose uptake in biofilm versus planktonic cells - Sousa, Cláudia (2008)
The aim of this work was to compare the glucose uptake of biofilms formed by four different Staphylococcus epidermidis strains as well as to compare between sessile and planktonic cells of the same strain. Biofilm cells showed a lower level of glucose uptake compared to planktonic cells. Moreover, glucose uptake by cells in the sessile form was strongly influenced by biofilm composition. Therefore, this work helps to confirm the phenotypic variability of S. epidermidis strains and the different behaviour patterns between sessile and free cells.